2022
DOI: 10.1111/hae.14556
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of physical exercise on postural balance in patients with haemophilia: A systematic review

Abstract: Introduction Balance training is important to improve balance and to decrease the risk of falls in patients with haemophilia (PWH). Aim To analyse the current knowledge about the effectiveness of physical exercise on postural balance in PWH. Methods A systematic search for clinical trials, published before November 2021, was conducted using the following electronic databases: PubMed/MEDLINE, Web of Science, Embase, Wiley Online Library and the Cochrane Central Register of Controlled Trials (CENTRAL). Two indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…The selected terms were combined using Boolean logical operators (OR, AND, NOT). In addition, a manual search of references included in previous systematic reviews was performed 8,18 . All references were analysed in Rayyan software (http://rayyan.qcri.org).…”
Section: Methodsmentioning
confidence: 99%
“…The selected terms were combined using Boolean logical operators (OR, AND, NOT). In addition, a manual search of references included in previous systematic reviews was performed 8,18 . All references were analysed in Rayyan software (http://rayyan.qcri.org).…”
Section: Methodsmentioning
confidence: 99%
“…12 In addition, increased proprioception and neuromuscular control have been demonstrated in PWH following postural stabilization training. 13 No study has been identified in the literature that investigated the effectiveness of an approach consisting of a core stabilization programme combined with CKC exercises on proprioception and physical activity in children with hemophilia.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, increased proprioception and neuromuscular control have been demonstrated in PWH following postural stabilization training 13 …”
Section: Introductionmentioning
confidence: 99%
“…The end result of this is impaired function and balance [9]. The imbalance could increase the risk of falls and kinesiophobia in this population, as well as favour a sedentary lifestyle, worsening musculoskeletal conditions and increasing the risk of bleeding and healthcare costs [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…This is why posture should be part of the routine evaluation in this population to allow the identification of dysfunction early and establish a tailored physical or rehabilitation program [18,19]. In this way, it will also be possible to better understand the joint conditions of the ankles and knees inpatients before surgery to more accurately recognise the effect of anexercise program on their balance [14]. The establishment of tailor-made exercise programs in haemophilia patients, which act on flexibility, strength, gait, and proprioception, helps to stop this negative cycle, protecting the joints from new bleeding episodes and improving patients' quality of life [18].…”
Section: Introductionmentioning
confidence: 99%